Identifying hotspots of hydro-hazards under global change: A worldwide review - Beevers, Lindsay; Popescu, Ioana; Pregnolato, Maria; Liu, Yuexiao; Wright, Nigel (Frontiers in Water, 2022)
Hydrological hazards (‘hydro-hazards’) are defined as extreme events associated with the occurrence, movement and distribution of water, specifically resulting in floods and droughts. As a result of global climate change these hazards are expected to change in the future, with areas of the globe becoming ‘hotspots’ for the intensification of these extremes. This paper is the first global review of the state- of-the-art research on hotspots for floods and drought. The work follows a systematic literature review of published research, and analyses and categorises the results of 122 published papers after a methodical screening process. The analysis highlighted the geographical areas where increasing hazards are anticipated, and those areas of the globe where no significant research has been published. The methods used to undertake the research are analysed and new trends identified. Potential avenues for future research are highlighted, including the incorporation of uncertainty analyses into hydro-hazard assessments, the consideration of multi-hazards and their interconnections, and finally the consideration of dynamic vulnerability and exposure in conjunction with changing hydro-hazards to understanding future risk.